(untitled) (UNIZIK Journal of STM Education, 2025)
The study investigated social intelligence as a predictor of secondary school students’ academic achievement in Chemistry in Cross River state, Nigeria. The study was guided by two research questions and two null hypotheses. The study adopted the predictive correlation research design. The population of the study was 6, 376 senior secondary two (SS2) students of Chemistry in the public secondary schools in Cross River State, from which 800 students were sampled for the study. The instrument for data collection was the Tromsø Social Intelligence Scale (TSIS), validated by three experts. The reliability the instrument was established using Cronbach Alpha with coefficient of internal consistency of 0.79. The instrument was administered to the students with the help of six research assistants. The data obtained was analyzed using simple and multiple linear regressions. The findings of the study revealed among others that 0.6percent of the variance in students’ Chemistry scores is predicted by social intelligence. Furthermore, achievement in chemistry were significantly predicted by social intelligence F(1, 2799) = 4.487, p < .05. It was recommended among others that, teachers should incorporate more collaborative and interactive activities in Chemistry classrooms to enhance students’ social skills.